Incidental Detection of Thyroid Nodule on Carotid Color Doppler Ultrasound in Patients Presenting with Cerebrovascular Diseases - Mazhar Shafiq; Shumaila; Tariq Jaffar; Sadaf Saleem; Akhter; Farrukh Nadeem; Muhammad Ali Mazhar (ziauddin University, 2024)
Background: Thyroid nodules are often detected in clinical practice, during physical examination, or accidentally during different imaging techniques. Most of these nodules are characterized as benign, and thyroid cancer is identified in only a small subclass. Ultrasonography is considered an important tool in thyroid nodule evaluation. Therefore, the study aimed to determine the frequency of incidental detection of a nodule of thyroid on carotid color Doppler ultrasound in patients presenting with cerebrovascular diseases. Methods: A cross-sectional descriptive study was carried out in the PNS Shifa hospital, Radiology department, from August 2017 to May 2018. Patients (n=110) underwent Color Doppler Ultrasound examinations with a scanner (Xario), furnished with a linear transducer operational at 10 MHz by the researcher. Incidental detection of thyroid nodule was labeled. Demographic detail including name, age, gender, and BMI was noted. Echogenicity and size of the thyroid gland was compared to that of encompassing glandular parenchyma. The data collected were analyzed and interpreted using SPSS version 20. Results: The patient's mean age was 59.92 ± 11.03 years with the ratio being 1.2:1 between males and females respectively. Diabetes and hypertension were existent in 43(39.1%) and 54(49.1%) patients respectively. Family history of thyroid nodules was present in 31(28.2%) patients. Thyroid nodule was detected in 34(30.91%) patients. The Benign pattern of thyroid nodules on grayscale. However, the histologic pattern of a mildly differentiated follicular thyroid carcinoma was detected. Conclusion: The frequency of incidental detection of thyroid nodule on carotid color Doppler ultrasound was 30.91% in patients presenting with cerebrovascular diseases. Keywords: Carotid Color Doppler Ultrasound; Incidental Detection; Cerebrovascular; Thyroid Nodule.